Unsteady boundary layer flow over a sphere in a porous medium - Nurul Farahain, Mohammad; Iskandar, Waini; Abdul Rahman, Mohd Kasim; Nurazleen, Abdul Majid (AIP Publishing, 2017)
This study focuses on the problem of unsteady boundary layer flow over a sphere in a porous medium. The governing equations which consists of a system of dimensional partial differential equations is applied with dimensionless parameter in order to attain non-dimensional partial differential equations. Later, the similarity transformation is performed in order to attain nonsimilar governing equations. Afterwards, the nonsimilar governing equations are solved numerically by using the Keller-Box method in Octave programme. The effect of porosity parameter is examined on separation time, velocity profile and skin friction of the unsteady flow. The results attained are presented in the form of table and graph.